1990
DOI: 10.1159/000200345
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Propranolol and Injection Sclerotherapy in the Long-Term Management of Variceal Bleeding

Abstract: Three treatment regimens were tried in 145 portal hypertensives with bleeding oesophageal varices to test the efficacy of each regimen in the prevention of rebleeding. Forty-seven cases received oral propranolol, 57 sclerotherapy, while 41 who did not receive any treatment except conservative management served as controls. Patients were followed up at 6 weeks, 6 months, 1 and 2 years to see the frequency of bleeding with each regimen. No significant difference was seen at 6 weeks with either of the three regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In the trial where propranolol was used to prevent recurrent gastrointestinal bleeding from portal hypertensive gastropathy, the percentage of patients who rebled was significantly lower in the propranolol group than in the control group. In the two trials performed in patients with noncirrhotic portal hypertension, the risk of rebleeding was significantly lower in patients receiving t-blockers for 1 or 2 years than in patients receiving a placebo [27,28]. No significant difference was found in the survival rate.…”
Section: Prevention Of Recurrent Gastrointestinal Bleedingmentioning
confidence: 92%
See 2 more Smart Citations
“…In the trial where propranolol was used to prevent recurrent gastrointestinal bleeding from portal hypertensive gastropathy, the percentage of patients who rebled was significantly lower in the propranolol group than in the control group. In the two trials performed in patients with noncirrhotic portal hypertension, the risk of rebleeding was significantly lower in patients receiving t-blockers for 1 or 2 years than in patients receiving a placebo [27,28]. No significant difference was found in the survival rate.…”
Section: Prevention Of Recurrent Gastrointestinal Bleedingmentioning
confidence: 92%
“…Among 14 trials comparing/3-adrenergic antagonists and placebo for the prevention of recurrent gastrointestinal bleeding, 12 were performed in patients with cirrhosis [2, 16--26] and 2 in patients with idiopathic portal hypertension or schistosomiasis [27,28]. The follow-up was I or 2 years.…”
Section: Prevention Of Recurrent Gastrointestinal Bleedingmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies on the secondary prevention of gastroesophageal bleeding in cirrhosis, P-blockade and sclerotherapy have been shown to have equivalent results on recurrent bleeding or overall mortality (1)(2)(3)(4)(5)(6)(7)(8). Some recent trials have suggested that propranolol can reduce recurrent gastroesophageal bleeding in cirrhotic patients treated with elective sclerotherapy (9)(10)(11)(12).…”
Section: ;16912-919)mentioning
confidence: 99%
“…Third, p-blockade significantly reduces the occurrence of recurrent gastroesophageal bleeding, death from recurrent bleeding and overall mortality (28) but is less effective in Child class C patients (17,19); however, propranolol has the advantage of being safe and costeffective. Fourth, sclerotherapy significantly reduces the risk of recurrent variceal bleeding and of mortality, and most comparative trials have shown both treatments to have nonsignificantly hfferent results (1)(2)(3)(4)(5)(6)(7)(8)36). However, one study suggested that apart from emergency treatment for bleeding, elective sclerotherapy had no effect on the prevention of recurrent variceal bleeding (37).…”
Section: 03mentioning
confidence: 99%